2020
DOI: 10.1002/admi.201902151
|View full text |Cite
|
Sign up to set email alerts
|

The C‐Terminal Domain of α‐Synuclein Confers Steric Stabilization on Synaptic Vesicle‐Like Surfaces

Abstract: While -Synuclein, an intrinsically disordered protein linked to Parkinson's disease, has been shown to associate with membrane organelles, its overall cellular function remains nebulous. -Synuclein binds to membranes through its amino-terminal domain (first ~ 100 residues), but there is no This article is protected by copyright. All rights reserved. 2 consensus on the biophysical function of the carboxyl-terminal domain (last ~ 40 residues) due, in part, to its lack of strong interaction partners and persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been suggested that the membrane binding domain in ␣-Syn senses membrane curvature; facilitates the formation or stabilizes a curvature on membrane structures [105]; or forms a tether between vesicles [101]. The acidic C-terminal region in ␣-Syn has been suggested to support and sterically stabilize curved membrane structures [106]. In accord with these reports, a role for ␣-Syn in the maintenance [107,108] and dynamics of SV pools has been reported [109,110].…”
Section: α-Syn Membrane Phospholipids and Pipmentioning
confidence: 78%
“…It has been suggested that the membrane binding domain in ␣-Syn senses membrane curvature; facilitates the formation or stabilizes a curvature on membrane structures [105]; or forms a tether between vesicles [101]. The acidic C-terminal region in ␣-Syn has been suggested to support and sterically stabilize curved membrane structures [106]. In accord with these reports, a role for ␣-Syn in the maintenance [107,108] and dynamics of SV pools has been reported [109,110].…”
Section: α-Syn Membrane Phospholipids and Pipmentioning
confidence: 78%